Effective cancer immunotherapy by Ganoderma lucidum polysaccharide-gold nanocomposites through dendritic cell activation and memory T cell response. (1st February 2019) - Zhang, Shulei; Pang, Guibin; Chen, Chao; Qin, Jianzhong; Yu, Huan; Liu, Yongming; Zhang, Xihui; Song, Zhentao; Zhao, Jian; Wang, Fujun; Wang, Yangyun; Zhang, Leshuai W.
Graphical abstract: Highlights: Immunoactive polysaccharide was incorporated with gold to form nanocomposite (GLP-Au). GLP-Au efficiently induced dendritic cell (DC) activation. GLP-Au strongly promoted the proliferation of CD4+ and CD8+ T cells via DC. GLP-Au inhibited 4T1 tumor growth and metastasis when combined with doxorubicin. Abstract: Polysaccharides purified from natural herbs possess immunoregulatory functions, while the efficacy of natural polysaccharides on cancer treatment remains unreliable, likely due to their low prescribed doses and fast clearances in clinical settings. In this study, gold nanocomposites containing Ganoderma lucidum polysaccharide (GLP-Au) efficiently induced dendritic cell (DC) activation, evident by the increase of CD80/CD86/CD40/MHCII, decrease of phagocytic ability and acid phosphatase activity, and increased cytokine transcription. GLP-Au significantly promoted the proliferation of CD4+ and CD8+ T cells in splenocytes. DC/T cell co-culture study proved that GLP-Au activation on DC directly resulted in T cell proliferation. GLP-Au exhibited strong inhibitory effects on 4T1 tumor growth and pulmonary metastasis when combined with doxorubicin. GLP-Au recovered body weight loss by doxorubicin and increased the percentage of CD4+/CD44+ memory T cells. This work suggests that polysaccharides from natural herbs can be incorporated into nanocomposites with immunoregulatory characteristics for enhanced efficacy on tumor therapy.